Fostering Religious Character and Environmental Awareness Through Scout Activities - Febriyanti M. Kiona; Burhanudin AK. Mantau; Fatimah Djafar; Alfadhli (Global Action and Education for Society, 2026)
This study aims to examine the instillation of religious character values and environmental awareness in Scouting activities at SDN 9 Mootilango in Gorontalo Regency, as well as to identify the challenges and solutions in their implementation. This study employs a qualitative method with a phenomenological approach. The data sources consist of primary and secondary data obtained through observation, interviews, and documentation. The informants in this study were the school principal, the Scout leader, the religious education teacher, and the students. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, while data validity was tested using source triangulation and method triangulation. The results of the study indicate that the instillation of religious character values in Scouting activities is carried out through the practice of praying before and after activities, performing prayers, memorizing daily prayers and short surahs, as well as fostering attitudes of honesty, discipline, politeness, responsibility, and mutual respect. Meanwhile, the instillation of environmental care character values is carried out through activities such as maintaining the cleanliness of the school environment, disposing of trash in designated areas, community service, and caring for plants on school grounds. The challenges faced in implementing the instillation of religious and environmental care character values include a lack of discipline among students and low awareness regarding environmental cleanliness. The solutions implemented by the school include continuous habit formation, setting a good example, and collaboration between the principal, the Scout leader, and the religion teacher. Thus, Scouting activities have proven to play a significant role in shaping religious and environmental values among students at SDN 9 Mootilango in Gorontalo Regency.